Application of the 9P Protocol in Organizing a High-Speed Shared Memory Buffer for Intermediate Computations (RAMPL) - Kulagin, A. K. (Programming and computer software, 2025)
In the context of the development of the modern economy, the scope of application of big data (databases, high-performance computing, and high-speed network channels), including automated methods for their processing (data system design, management, and monitoring), rapidly expands. Artificial intelligence systems become especially popular as methods for automation of all aspects of big data use. In the Russian Federation, ambitious tasks in this field of computer science are currently solved. Despite a number of systemic problems, a distributed network of supercomputer centers for collective use is formed in Russia, with the aim of rationalizing the use of supercomputing resources. There are advances in the development of technologies for writing and translating parallel software. This paper provides a brief overview of the software solutions used in the Plan 9 operating system. In particular, the network protocol of the 9P file system is considered and compared with NFS (current version). Based on this protocol, the author proposes a software architecture that implements rapid access for multi processing and learning (RAMPL) during intermediate computations, which is necessary for the optimization of numerical methods and machine learning in distributed computing systems. In addition, the author uses this protocol to organize the monitoring of remote hosts, as well as control processes and devices on them. The paper also outlines some tasks aimed at improving the 9P network protocol. Some comments on the features of the protocol in its current version are provided. It is concluded that the technologies based on it have great potential.